Effects of 6-benzylaminopurine, sucrose and agar on in vitro vitrification of pear tree - Pasqual, Moacir; Lopes, Patrícia Andrade; Arello, Eduardo Fonseca; Barros, Inacio de (Pesquisa Agropecuaria Brasileira, 1991)
The effects of 6-benzylaminopurine (BAP), sucrose and agar on in vitro vitrification of Pyrus calleryana L. shoots were studied. Vitrified shoots maintained by tissues culture on 'MS' medium supplemented with BAP 1.0 mg/l were transferred to test tubes containing MS medium supplemented with all of the possible combinations of BAP (0.0; 0.5; 3.0; 5.5 and 8.0 mg/l) and sucrose (0; 30; 60 and 90 g/l), and BAP (0.0; 0.5; 3.0; 5.5 and 8.0 mg/l) and agar (3; 6 and 9 g/l). They were incubated under 16 h photoperiod (3.000 lux) and at 27°C temperature. The most developed new shoots were observed in absence of BAP and sucrose. BAP in absence of sucrose did not affect the number of normal shoot production. When sucrose was present in the medium, the production of normal shoots was higher with BAP absence and lower BAP concentration. The highest frequency of shoot vitrification was registred at the highest BAP concentration. The agar concentrations did not affect the formation of vitrified shoots.